‘신고’배 재배지 내 수체 및 토양의 탄소 및 질소 저장량 - 이태규(Tae-Kyu Lee); 최장전(Jang-Jeon Choi); 김종성(Jong-Sung Kim); 이한찬(Han-Chan Lee); 노희명(Hee-Myong Ro) (Weon'ye gwahag gi'sulji, 2013)
To report country-specific carbon and nitrogen stocks data in a pear orchard by Tier 3 approach of 2006 IPCC guidelines for national greenhouse gas inventories, an experimental pear orchard field of the Pear Research Station, National Institute of Horticultural & Herbal Science, Rural Development Administration, Naju, Korea ($35^{°}01^{′}27.70N$, $126^{°}44^{′}53.50^{′′}E$, 6 m altitude), where 15-year-old 'Niitaka' pear (Pyrus pyrifolia Nakai cv. Niitaka) trees were planted at a $5.0m{×}3.0m$ spacing on a Tatura trellis system, was chosen to assess the total amount of carbon and nitrogen stocks stored in the trees and orchard soil profiles. At the sampling time (August 2012), three trees were uprooted, and separated into six fractions: trunk, main branches, lateral branches (including shoots), leaves, fruits, and roots. Soil samples were collected from 0 to 0.6 m depth at 0.1 m intervals at 0.5 m from the trunk. Dry mass per tree was 4.7 kg for trunk, 13.3 kg for main branches, 13.9 kg for lateral branches, 3.7 kg for leaves, 6.7 kg for fruits, and 14.1 kg for roots. Amounts of C and N per tree were respectively 2.3 and 0.02 kg for trunk, 6.4 and 0.07 kg for main branches, 6.4 and 0.09 kg for lateral branches, 6.5 and 0.07 kg for roots, 1.7 and 0.07 kg for leaves, and 3.2 and 0.03 kg for fruits. Carbon and nitrogen stocks stored between the soil surface and a depth of 60 cm were 138.29 and $13.31Mg{·}ha^{-1}$, respectively, while those contained in pear trees were 17.66 and $0.23Mg{·}ha^{-1}$ based on a tree density of 667 $trees{·}ha^{-1}$. Overall, carbon and nitrogen stocks per hectare stored in a pear orchard were 155.95 and 13.54 Mg, respectively. IPCC 2006 guideline에서 제시한 Tier 3 수준에 맞게 배나무 과수원의 온실가스 저장량을 산정하기 위하여, 전라남도 나주에 위치한 농촌진흥청 배시험장 재배포장($35^{°}01^{′}27.70N$, $126^{°}44^{′}53.50^{′′}E$, 표고 6m)에 $5.0{×}3.0m$ 간격으로 재식된 Y자 수형의 15년생 배 '신고(Pyrus pyrifolia Nakai cv. Niitaka)' 재배지를 대상으로 과수와 재배지 토양의 총 탄소 및 질소 저장량을 측정하였다. 이를 위해 2012년 8월, 3반복으로 과수를 굴취하여 주간, 주지, 측지, 잎, 과일, 뿌리로 분류하였고, 과수 주간으로부터 약 0.5m 떨어진 지점에서 0.6m 깊이까지 0.1m 간격으로 토양을 채취하였다. 나무 한그루당 건물중은 주간이 4.7kg, 주지가 13.3kg, 측지가 13.9kg, 잎이 3.7kg, 과일이 6.7kg, 뿌리가 14.1kg이었다. 단위 질량당 총 탄소 및 질소의 함량은 주간에서 각 2.3kg과 0.02kg, 주지에서 6.4kg과 0.07kg, 측지에서 6.4kg과 0.09kg, 뿌리에서 6.5kg과 0.07kg, 잎에서 1.7kg과 0.07kg, 과일에서 3.2kg과 0.03kg 이었다. 재식밀도(667trees/ha)를 기준으로, 탄소와 질소는 재배지 토양에 각각 138.29 및 $13.31Mg{·}ha^{-1}$가 저장되어 있었고, 과수에 각각 17.66 및 $0.23Mg{·}ha^{-1}$씩 보유되어 있었다. 이를 종합한 결과 과수 재배지에서 탄소는 $155.95Mg{·}ha^{-1}$, 질소는 $13.54Mg{·}ha^{-1}$가 저장되어 있었다.